2009
DOI: 10.1029/2008jf001088
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and analytical models of cosmogenic radionuclide dynamics in landslide‐dominated drainage basins

Abstract: [1] In many tectonically active regions on Earth, landslides dominate sediment delivery to channels. While cosmogenic radionuclides (CRN) represent a valuable tool to document basin-averaged erosion rates, a better understanding of CRN dynamics in these systems is required before erosion rates can be reliably inferred from CRN concentrations. The stochastic nature of landslides results in variability of CRN concentrations in both alluvial and hillslope samples that is both difficult to document and poorly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
225
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(243 citation statements)
references
References 40 publications
13
225
1
3
Order By: Relevance
“…Our approach differs considerably from the way Yanites et al (2009) assess the effect of storage of land slide-derived material in a river basin. In their model, Yanites et al (2009) consider the effects of sediment storage on cosmogenic 10 Be nuclide concentrations in erosional settings, where landslide material is usually prone to storage before it is removed by rivers and in the process is mixed with material from source area erosion processes.…”
Section: Model Setupmentioning
confidence: 87%
See 1 more Smart Citation
“…Our approach differs considerably from the way Yanites et al (2009) assess the effect of storage of land slide-derived material in a river basin. In their model, Yanites et al (2009) consider the effects of sediment storage on cosmogenic 10 Be nuclide concentrations in erosional settings, where landslide material is usually prone to storage before it is removed by rivers and in the process is mixed with material from source area erosion processes.…”
Section: Model Setupmentioning
confidence: 87%
“…In their model, Yanites et al (2009) consider the effects of sediment storage on cosmogenic 10 Be nuclide concentrations in erosional settings, where landslide material is usually prone to storage before it is removed by rivers and in the process is mixed with material from source area erosion processes. In contrast to the Yanites et al study, which addresses storage effects near the sediment source in very small catchments, the focus of our analysis is on sediment reworking by lateral channel migration.…”
Section: Model Setupmentioning
confidence: 99%
“…These estimates are subject to large uncertainty due in part to the narrow grain size range investigated here. Many authors (Brown et al, 1995;Belmont et al, 2008;Niemi et al, 2005) have suggested that stochastic processes such as the large-scale rockfalls and debris flows produce different grain size distributions and potentially different cosmogenic nuclide concentrations than in creep-dominated landscapes (Yanites et al, 2009). However, the large difference between the denudation rates recorded for the landslide dominated basins vs. the soil creep dominated basins suggests that our grain size fractions do include this signal.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, modern landslides in the Goms occur within the thin soil mantled zone. Therefore, the perturbations to denudation rates due to the occurrence of deep-seated landslides should not be a significant factor here (Niemi et al, 2005;Yanites et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is also increasingly recognized that CWDRs are affected by a number of site-specific biases and limitations that prevent us from simply reading denudation rates from a bag of sand. Amongst others, landsliding, a dominant erosion process in actively eroding landscapes, violates the steadystate denudation assumption and may thus lead to biases in the CWDR (Niemi et al, 2005;Yanites et al, 2009). The stochastic nature of sediment supply to the channels and hydrology within the river network may also perturb the TCN signal over a range of timescales and limits our ability to use a single sediment sample as a representative and accurate representative of upstream erosion products (Kober et al, 2012;Lupker et al, 2012;West et al, 2014;Foster and Anderson, 2016).…”
Section: Introductionmentioning
confidence: 99%